Crop-Weather Models During the â€œKharif Seasonâ€ under the Rainfed Conditions of Hissar Region - Bishnoi, O P (Annals of Arid Zone, 2016)
The Kharifcrop-weather models have been prepared utilising the water availability periods, the climatic water balance parameters, the accumulated soil moisture, weather parameters and the performance of the Kharif crops under the different climatic situations prevailing during the above normal, normal and sub-normal years of rainfall. Crop production strategy has been suggested for each of these situations.